Poésie/collage : Deux modalités du faire dans le champ de l’autre - Claudine Armand (Revue LISA)
Anne Ryan’s bifocal work, which combines linguistic and iconographic approaches, engages in a continual examination of the limits of artistic expression and explores the porous border between two heterogeneous semiotic codes. Driven by the same desire to express an inner experience and to explore the complex relationship between the I and the others, the author has shifted from poetry and short story writing to engraving and collage. However, even when she worked essentially in graphic arts, she was never able to abandon her favorite mode of expression, verbal language. Words resurface in her collages, either in a fragmented and obtrusive way reminiscent of Cubist paintings, or in a more subdued way as in a palimpsest. There is something paradoxical about her artistic output as her handling of verbal language is based on tradition and literary conventions whereas her plastic work is characterized by experimentation, innovation, and disruption.